BREASTFEEDING HISTORY AND FERTILITY DRUGS USE OF BREAST CANCER INCIDENCE OF PATIENTS AT THE HOSPITAL: A CASE-CONTROL STUDY - Dian Ratnasari; Noor Hidayah; Fitriana Kartikasari ((IJP) Indonesia Jurnal Perawat, 2025)
Breast cancer is a malignancy that is frequently diagnosed in women and is the leading cause of cancer-related deaths worldwide. Based on previous studies, a history of not breastfeeding and the use of fertility drugs are suspected risk factors for breast cancer in women. This study aims to determine the risk factors of breastfeeding history and the use of fertility drugs for breast cancer among cancer and non-cancer patients at RS Tk. II Dr. Soedjono Magelang.This research employs a quantitative case-control study design. The primary data used in this study are medical records of women visiting the oncology clinic, inpatient ward, and chemotherapy unit at RS Tk. II Dr. Soedjono Magelang over five weeks from December 20, 2024, to January 25, 2025. A total of 228 women aged 20 to 86 years were identified, including 76 breast cancer patients. The control group in this study consisted of 152 non-breast cancer patients, with a case-to-control ratio of 1:1. A total of 76 control data points were randomly selected from the 152 non-cancer patients. Data collection was conducted using a questionnaire that covered breastfeeding history, history of fertility drug use, and breast cancer diagnosis, categorized as either 'yes' or 'no.' Data analysis was performed using univariate analysis (percentage) and bivariate analysis with the chi-square test. The study results showed a significant association between breastfeeding history and breast cancer, with a p-value of 0.006 and an odds ratio (OR) of 2.49. This means that mothers with a history of not breastfeeding have a 2.49 times higher risk of developing breast cancer compared to those who have a history of breastfeeding.